2016
DOI: 10.1097/hmr.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home report card and performance gap

Abstract: The significant gap implies that administrators either do not regularly review the NHC report card or do not concur with the NHC ratings. To reduce the gap and thereby improve performance, it is necessary to stabilize the administrators' position so that administrators know how they stand in the market and are consequently better equipped to successfully respond to the market. Facilities may also need to provide regular training on current technologies and facilitate use of the NHC report card, targeting admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A perhaps inevitable area of concern with the NHC measures is inadequate risk-adjustment. Most providers feel that risk-adjustment could be improved and that lack of adequate risk-adjustment means that their nursing home is not accurately represented on NHC (A. S. Kim, 2016b; Perraillon et al., 2017). The staffing measures and many of the clinical quality measures incorporate some risk-adjustment, while the inspections rating is not risk-adjusted.…”
Section: Resultsmentioning
confidence: 99%
“…A perhaps inevitable area of concern with the NHC measures is inadequate risk-adjustment. Most providers feel that risk-adjustment could be improved and that lack of adequate risk-adjustment means that their nursing home is not accurately represented on NHC (A. S. Kim, 2016b; Perraillon et al., 2017). The staffing measures and many of the clinical quality measures incorporate some risk-adjustment, while the inspections rating is not risk-adjusted.…”
Section: Resultsmentioning
confidence: 99%
“…The CHIEF is an adaptation of Donabedian’s classic structure–process–outcome (SPO) framework tailored to the community benefit strategy implementation context and expanded to address previously noted limitations of the SPO framework. For example, the SPO is a framework to evaluate medical care, particularly care that is encapsulated in the physician–patient interaction (Beauvais et al, 2021; Castle et al, 2015; Donabedian, 2005; Garman et al, 2011; Hefner et al, 2022; Hogan et al, 2022; Kim, 2016; Lane et al, 2014; Mchugh et al, 2016; Upadhyay et al, 2021). In contrast, nonprofit hospital community benefit strategies should operate at a community or population level and shift from medical care to addressing social determinants and health promotion.…”
Section: Theorymentioning
confidence: 99%
“…The higher the market concentration of a nursing home, the higher its quality of care. 20,21 For example, rates of catheter use, body restriction, and lack of toileting were lower in such facilities. 22 Conversely, Yuan et al 18 noted that nursing homes located in an area with high market demand-such as one with a high proportion or population of older adults-and low competition had relatively lower quality scores.…”
Section: External Factorsmentioning
confidence: 99%
“…31 In a similar vein, high turnover rates of nurse aides in nursing homes has been demonstrated to be associated with higher rates of pressure ulcers and urinary tract infections among residents. [32][33][34] Sufficient nurse staffing has also been reported to be associated with better outcomes, such as lower rates of mortality and readmission to acute care hospitals, 32 smaller discrepancy between self-rated and government-rated performance, 20 lower rates of pressure ulcers and urinary tract infections, 35 and adequate daily care. 36 However, one study indicated that staffing rating could not predict rates of readmission or mortality.…”
Section: Organizational Factorsmentioning
confidence: 99%